Trade and safety issues of raw beef from the countryside of Bahia state, Brazil - Permínio Oliveira Vidal Júnior; Ana Cláudia Rios Menezes; Lícia Milena Pereira Souza; Alaíse Gil Guimarães; Ryzia de Cassia Vieira Cardoso (SAGE Publishing, 2020)
Background: Brazil is one of the world's largest meat exporters. However, there is a paradox in this situation due to existing non-inspected meat trade and technical-sanitary failures in retail marketing.  Design and methods: This study aimed at characterizing the issues of trade, food safety and quality of raw beef in the street market of a municipality in the state of Bahia. An exploratory, quantitative and census study was carried out, at 17 raw beef vending locations. A questionnaire was administered and meat samples were collected (n=34), which were submitted to a physicochemical assessment, color analysis and microbiological analyses. Results: Meat sellers were between 20 and 64 years of age, predominantly males (82.4%), with limited education and without professional training (64.7%). Medians for temperature and pH in the small butcher shops samples were 18.10ºC and 5.75 respectively, and 21.80ºC and 5.50, in small supermarkets samples. The difference in pH was significant (p<0.05). The filtration test suggested quality changes in 17.65% of the samples. No frauds were detected. Total coliform count medians were 4.90 and 4.78 log CFU/g, for the samples taken from butcher shops and supermarkets, respectively. E. coli was identified in approximately 40.0% of the samples. Salmonella spp. were confirmed in two samples collected in the butcher shops. There was a significant association between inadequate storage conditions and microorganism counts (p<0.02). Conclusions: The results evidenced a meat supply with preservation failures and non-compliance with hygiene requirements, constituting a consumers' health hazard, not in line with an agro-exporting country model.